Learning to look at modern art - Acton, Mary (Oxon; Routledge- Taylor and Francis Group, 2004)
A guide to the visual understanding, history and analysis of modern art. Covers topics such as Expressionism, Constructivism, the Bauhaus, Surrealism, Pop art, Conceptual Art, young British Art.
English
Keywords: Modern Era; N5300-7418 Visual Arts- History